Fecal Proteomic Analysis in Healthy Dogs and in Dogs Suffering from Food Responsive Diarrhea - Matteo Cerquetella; Giacomo Rossi; Andrea Spaterna; Beniamino Tesei; Alessandra Gavazza; Graziano Pengo; Stefania Pucciarelli; Luca Scortichini; Gianni Sagratini; Massimo Ricciutelli; Andrea Marchegiani; Silvia Vincenzetti (The Scientific World Journal)
Different laboratory markers are routinely used in the diagnosis and management of gastrointestinal (GI) disease in dogs. In the present study, starting from feces from both healthy dogs and dogs suffering from food responsive diarrhea (FRD), we tried to find proteins differently expressed in the two groups of dogs, by using a proteomic approach. Interestingly, we found that the immunoglobulin J-chain isoform 1 (species: Canis lupus familiaris) was identified only in diseased dogs (not in healthy). J-chain combines especially IgA monomers to IgA dimers and plays a crucial role for their secretions into mucosal interface. Being the first study of that kind in the dog, it is only possible to hypothesize that their presence could be likely due to an increased activation of the immune system or to a mucosal damage or both in FRD patients. Similarly, it is still impossible to assess whether this protein could be used as diagnostic/prognostic marker of GI disease; however, this study represents a promising first step toward fecal proteomics in canine GI disorders.